DYNAMIC CENTRIOLAR LOCALIZATION OF POLO AND CENTROBIN IN EARLY MITOSIS PRIMES CENTROSOME ASYMMETRY - Gallaud, Emmanuel; Nair, Anjana Ramdas; Horsley, Nicole; Monnard, Arnaud; Singh, Priyanka; Pham, Tri Thanh; Garcia, David Salvador; Ferrand, Alexia; Cabernard, Clemens (Public Library of Science, 2020)
Centrosomes, the main microtubule organizing centers (MTOCs) of metazoan cells, contain an older “mother” and a younger “daughter” centriole. Stem cells either inherit the mother or daughter-centriole-containing centrosome, providing a possible mechanism for biased delivery of cell fate determinants. However, the mechanisms regulating centrosome asymmetry and biased centrosome segregation are unclear. Using 3D-structured illumination microscopy (3D-SIM) and live-cell imaging, we show in fly neural stem cells (neuroblasts) that the mitotic kinase Polo and its centriolar protein substrate Centrobin (Cnb) accumulate on the daughter centriole during mitosis, thereby generating molecularly distinct mother and daughter centrioles before interphase. Cnb’s asymmetric localization, potentially involving a direct relocalization mechanism, is regulated by Polo-mediated phosphorylation, whereas Polo’s daughter centriole enrichment requires both Wdr62 and Cnb. Based on optogenetic protein mislocalization experiments, we propose that the establishment of centriole asymmetry in mitosis primes biased interphase MTOC activity, necessary for correct spindle orientation.
Keywords: Centrioles; Centrosomes; Neuroblasts; Cell cycle and cell division; Mitosis; Green fluorescent protein; Microtubules; Prophase; Research Subject Categories::NATURAL SCIENCES::Biology; Type of access: Open Access